Respuesta :
Explanation:
Change in velocity can be calculated by subtracting initial velocity from final velocity. The expression for the same is as follows.
[tex]\Delta v = v_{f} - v_{i}[/tex]
where, [tex]\Delta v[/tex] = change in velocity
[tex]v_{f}[/tex] = final velocity
[tex]v_{i}[/tex] = initial velocity
It is given that initial velocity is +30 m/s and final velocity is -40 m/s. Thus, calculate the change in velocity as follows.
[tex]\Delta v = v_{f} - v_{i}[/tex]
= -40 m/s - (+30 m/s)
= (-40 - 30) m/s
= -70 m/s
Therefore, the change in the velocity -70 m/s.